An empirical study on intercultural contact and intercultural communication competence of Chinese international students in the UK: A case study of Lancaster University - Lu, Jingjing; Guénier, Amily D. Wang; Hird, Derek (Journal of International Students, 2025)
This study explores the relationship between intercultural contact (IC) and intercultural communication competence (ICC) among Chinese international students at Lancaster University, UK. Using a mixed-methods approach, the research analyzes the frequency and nature of IC and self-assessed ICC levels.Findings reveal a predominance of indirect IC, such as media consumption and cultural events, over direct interactions with native English speakers. Self-assessment of ICC indicates strong attitudes towards cultural diversity but identifies areas for improvement in domestic cultural knowledge and cognitive skills.Statistical analysis demonstrates a significant positive correlation between IC and ICC, with direct IC positively impacting communication skills and indirect IC contributing to cultural knowledge and positive attitudes.These findings emphasize the importance of both direct and indirect IC in developing ICC. Educational institutions should focus on facilitating diverse IC opportunities to enhance students’ language proficiency, cultural adaptation, and overall well-being.